البعد التداولي لقضية التعريف والتنكير - دندوقة, فوزية (جامعة الوادي - University of Eloued, 2021)
نسعى من خلال هذا المقال أن نعالج قضية التعريف والتنكير في اللغة العربية من منظور تداولي، بعقد مقارنة بين ما جاء به النحاة العرب، وما قال به التداوليون في الدرس الغربي، ففي ظل ازدهار النظريات الغربية الحديثة نحاول أن نكشف عن بعض مكنونات تراثنا التي تبين عن وعي فكري سابق متميز. وذلك بالإجابة عن الإشكالية الجوهرية التي حددت منطلقا للدراسة وهي: ما هي الأبعاد التداولية لقضية التعريف والتنكير؟ Abstract: Through this article, we seek to address the issue of definition and denial in the Arabic language from a pragmatic perspective, by comparing what the Arab grammarians came with, and what the pragmatists said in the Western lesson. Distinguished prior intellectual awareness. By answering the fundamental problem that identified a starting point for the study, which is: What are the deliberative dimensions of the issue of definition and denial? Key words: Pragmatics, definition, denunciation, Arabic language.
مقال
Keywords: التداولية، التعريف، التنكير، اللغة العربية